ETMR-08. INTERNATIONAL CONSENSUS PROTOCOL FOR EMBRYONAL TUMOR WITH MULTILAYER ROSETTES. (4th December 2020) - Hanson, Derek; Andre, Nicolas; Chi, Susan; Filbin, Mariella; Fisher, Michael; Hoffman, Lindsey; Khatib, Ziad; Kool, Marcel; Narendran, Aru; Pizer, Barry; Slavc, Irene; Vogel, Timothy; et al.
Abstract: Embryonal tumors with multilayer rosettes (ETMR) are rare and highly-aggressive central nervous system (CNS) neoplasms which occur primarily in young children and carry a dismal prognosis. To date, no large clinical investigations have been conducted to determine the optimal therapy for ETMR. Data from retrospective case series suggest that our most aggressive standard therapies are not sufficient for cure in the majority of cases. New treatment approaches incorporating pre-clinical data and the known biology of ETMR are therefore urgently needed. A German drug screen using the patient-derived ETMR BT183 cell line and its xenograft revealed anti-tumor activity of topotecan, doxorubicin, and actinomycin D; three agents used infrequently for treating infant CNS tumors. Additional results from a small series of ETMR patients suggest that optimization of induction chemotherapy using these active agents may improve response and survival outcomes. In 2019, an international panel of pediatric neuro-oncology experts convened to advance therapy for ETMR. A consensus protocol was developed incorporating maximal safe surgical resection, induction chemotherapy with active pre-clinical agents, intrathecal chemotherapy, radiotherapy, and high-dose chemotherapy. This international consensus protocol represents the first prospective clinical investigation specific to ETMR and will be available through a treatment registry globally and as a clinical trial at select centers. The study aims to improve survival by providing aggressive, optimized therapy for ETMR and will serve as a platform to explore new biologically-promising agents. The investigation will also provide valuable prospective outcome data and correlative biological studies to serve as baseline comparators for future clinical trials.